2013
DOI: 10.4103/0973-1482.119349
|View full text |Cite
|
Sign up to set email alerts
|

Carotid sparing hypofractionated tomotherapy in early glottic cancers: Refining image guided IMRT to improve morbidity

Abstract: Carotid sparing was possible using cstomo plans with significantly better conformity. Applying AS5 could enable us to reduce the PTV (3 mm) margin in X, Y axes for the remaining 15 fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Target and OAR were contoured based on the guideline of University of Florida as summarized in Table 1 [ 5 ]. Clinical target volume (CTV) was contoured; superiorly, to include the most cranial extent of the arytenoid cartilage, inferiorly, to include from 1 to 1.5 cm below the level of the true vocal cords, posteriorly, to include the arytenoid cartilage and posterior commissure, and anteriorly and laterally, to include the anterior commissure while excluding the thyroid cartilage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Target and OAR were contoured based on the guideline of University of Florida as summarized in Table 1 [ 5 ]. Clinical target volume (CTV) was contoured; superiorly, to include the most cranial extent of the arytenoid cartilage, inferiorly, to include from 1 to 1.5 cm below the level of the true vocal cords, posteriorly, to include the arytenoid cartilage and posterior commissure, and anteriorly and laterally, to include the anterior commissure while excluding the thyroid cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…where treatment volume is defined as the volume irradiated more than 95% of the prescription dose [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“… 7 In this context, the dosimetric and clinical research on the so-called intensity-modulated radiotherapy (IMRT) or tomotherapy based “carotid-sparing radiotherapy technique” has demonstrated that it was plausible to reduce the CAs doses to meaningfully lower levels with no negative impact on the target dose coverage in early-stage laryngeal carcinoma patients. 2 , 3 , 8 - 12 …”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, various treatment techniques have been introduced to decrease the dose administered to CA during RT for EGC [ 6 - 9 ]. Intensity-modulated radiation therapy (IMRT) can maintain good coverage while significantly reducing the dose administered to the CA, as compared with traditional LOF and 3-dimensional conformal RT (3DCRT) [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intensity-modulated radiation therapy (IMRT) can maintain good coverage while significantly reducing the dose administered to the CA, as compared with traditional LOF and 3-dimensional conformal RT (3DCRT) [ 6 - 8 ]. Further, Chatterjee et al [ 9 ] have reported that helical tomotherapy-based IMRT offers significant improvements to CA sparing. Inverse planning–based IMRT is highly effective in reducing the dose to adjacent organ at risks (OAR) and improves target dose conformity by controlling the beam intensity.…”
Section: Introductionmentioning
confidence: 99%